How a farming environment protects from atopy. (October 2019) - Deckers, Julie; Lambrecht, Bart N; Hammad, Hamida
Highlights: Growing up in farms protect from developing allergies later in life. Farm-induced protection is mediated by a gene–environment interaction. Farm dust components confer protection by acting on both barrier and immune cells. Abstract : It is now well established that the exposure to certain environments such as farms has the potential to protect from the development of allergies later in life. This protection is achieved when repeated exposure to the farming environment occurs early in life, but persists when children spend sufficient amount of time in contact with livestock and hay, and drink unpasteurized milk. The capacity of farm dust to protect from allergy development lies, amongst others, in the microbe composition in the farm. These protective microbes release various metabolites and cell wall components that change farmers' home dust composition, when compared to urbanized home dust. Additionally, they can colonize various barrier sites (skin, lung, intestine) in farmers' children, leading to persistent changes in the way their immune system and their barrier cells respond to environmental allergens.